International seminar on traditional cultures in South-East Asia (Bombay, 1960)
The Regional Meeting of Experts on Traditional Cultures in South-East Asia sponsored by Unesco and conducted with its aid by the Institute from November 3-7, 1958, is virtually the fruition of the project Unesco conceived at its General Conference at Montevideo in 1954 "to organize or encourage with the assistance of Member States and their National Commissions. . . studies and round table discussions con cerning the development of the cultural life of the com munities" (Resolution 4.31). This move was the reflection of a growing concern for the preservation and promotion of the best elements in the traditional cultures of South-East Asia, which, it was realized, were apt to be ignored or affected adversely in the impact of a rapid industrialization of the underdeveloped countries of South-East Asia. Un doubtedly, these countries have great need to command the benefits of modern science and technology to improve their economy and obtain better standards of living; but the manner of attaining these benefits and the pace of the process are bound to affect the cherished values and institu tions of the ancient cultures of these lands, and the situation calls for study with a view to guide the process along lines calculated to secure optimum success in blending the best features in the new and old cultures. The efforts of Unesco in this direction comprised, on the one hand, the organiza tion of seminars at University level and on the other the institution of field studies by competent persons. It was to evaluate the results of this two-sided approach and to tackle the problem from a practical point of view that the Regional Meeting of Experts was summoned. They came from Indonesia, Ceylon, and India. Unfortunately Burma could not send her expert. Delegates and special invitees readily accepted the invitation of the Institute to help in the objective of the meeting. Details of the participants in the seminar are given in the appendix.
Keywords: Sociology